AGR313: Principles of Agricultural Marketing / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2018)
This course discuss various process, problems, issues and challenges related to Malaysia agricultural commodity crops such as oil palm, rubber, paddy, cocoa and other industrial crops. It is also discover the ways to manage those problems arise from the process marketing of these agricultural commodity crops.